Patellofemoral Joint Replacement and Nickel Allergy: An Unusual Presentation. (12th October 2015) - Syed, Farhan; Jenner, Edward; Faisal, Mohammad
Abstract : Metal allergy is an unusual complication of joint replacement that may cause aseptic loosening and necessitate joint revision surgery. We present the case of nickel allergy causing aseptic loosening following patellofemoral joint replacement (PFJR) in a 54-year-old male. Joint revision surgery to a nickel-free total knee replacement was performed with good results. Our literature review shows that there is no evidence to guide the management of metal allergy in PFJR. The evidence from studies of total knee replacement is limited to retrospective case series and case reports and gives contradictory recommendations. The optimal management strategy for metal allergy in PFJR is not clear. We recommend allergy testing in patients with history of metal allergy and use of an allergen-free implant in those with positive tests. As there is no gold standard test to establish metal allergy, the choice of test should be guided by availability and recommendation from the local unit of dermatology and allergy testing. We recommend investigation for metal allergy in patients with implant loosening where other causes have been excluded.